2020
DOI: 10.1037/hea0000826
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trajectories of depression symptoms in mothers of children with cancer.

Abstract: Objective: To identify trajectories of depression symptoms in mothers of children with cancer from diagnosis/relapse through 5 years and examine maternal factors at diagnosis/relapse predicting membership in these trajectories. Method: Mothers (n ϭ 327; M age ϭ 37.6 years, SD ϭ 7.7 years; 85.9% White) reported depression symptoms near the time of their child's diagnosis/relapse and then again at 1-, 3-, and 5-years postdiagnosis/relapse. Mothers also reported perceived stress, coping (primary control, secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 47 publications
(115 reference statements)
4
22
0
Order By: Relevance
“…Our findings add to a growing body of literature suggesting that most caregivers of children with cancer are resilient when faced with the challenge of their child's illness 17,19 . This notion coincides with longitudinal studies of caregiver distress, which suggests that most caregivers adjust to the stressor of pediatric cancer treatment within the first year and continue to do well over time 9,15 . A subset of caregivers who struggle to adjust initially may be at highest risk for long‐term elevations in psychological symptoms 15,22 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings add to a growing body of literature suggesting that most caregivers of children with cancer are resilient when faced with the challenge of their child's illness 17,19 . This notion coincides with longitudinal studies of caregiver distress, which suggests that most caregivers adjust to the stressor of pediatric cancer treatment within the first year and continue to do well over time 9,15 . A subset of caregivers who struggle to adjust initially may be at highest risk for long‐term elevations in psychological symptoms 15,22 .…”
Section: Discussionsupporting
confidence: 80%
“…This notion coincides with longitudinal studies of caregiver distress, which suggests that most caregivers adjust to the stressor of pediatric cancer treatment within the first year and continue to do well over time 9,15 . A subset of caregivers who struggle to adjust initially may be at highest risk for long‐term elevations in psychological symptoms 15,22 . A deeper understanding of individual as well as familial differences in effective coping and support strategies may improve intervention for these caregivers 40 .…”
Section: Discussionsupporting
confidence: 66%
“…In addition to mothers' reduced quality of care, this issue also affects their quality of life. Howard Sharp reported that caring alone caused depression in mothers of children with cancer in the longrun ( 28 ). Thuy showed that family support was related to fatigue of mothers ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data presented are part of a longitudinal study examining coping and family communication following a new or relapsed diagnosis of childhood cancer 5,15,16 . Participants eligible for the larger study were (a) 5‐17 years old, (b) diagnosed with new or relapsed cancer, (c) English‐speaking, and (d) without preexisting developmental delay.…”
Section: Methodsmentioning
confidence: 99%
“…Data presented are part of a longitudinal study examining coping and family communication following a new or relapsed diagnosis of childhood cancer. 5,15,16 Participants eligible for the larger study were (a)…”
Section: Methodsmentioning
confidence: 99%